2009
DOI: 10.1002/masy.200951224
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Temperatures on PET‐Concrete Properties

Abstract: Lightweight aggregate is an important material in reducing the unit weight of concrete and it is essential in the construction of high‐rise buildings; besides, the use of recycled PET bottles as lightweight aggregate in concrete is an effective contribution for environmental preservation. So, the objective of the present work is to study the flexural strength of PET‐concrete and PET thermal degradation in the concrete, when the blends with 10 and 20 vol% of PET are exposed to different temperatures (200, 400, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…The minor changes in flexural strength were accredited to the elastic behavior of the PW (Hannawi et al, 2010). Albano et al Albano et al (2009) observed that the enclosure of PET in concrete decreased the splitting tensile strength owing to the increase in the porosity. Abdel Moti, H. M., and Mustafa, M. A. Abdel Moti and Mustafa (2019) Stated that the splitting tensile strength was reduced by 10.15% and 14.03% for the 5% and 10% respectively compared to the control mix.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The minor changes in flexural strength were accredited to the elastic behavior of the PW (Hannawi et al, 2010). Albano et al Albano et al (2009) observed that the enclosure of PET in concrete decreased the splitting tensile strength owing to the increase in the porosity. Abdel Moti, H. M., and Mustafa, M. A. Abdel Moti and Mustafa (2019) Stated that the splitting tensile strength was reduced by 10.15% and 14.03% for the 5% and 10% respectively compared to the control mix.…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, discovering new alternatives is crucial to arise sustainability in the construction industry. Researchers studied the usage of wastes as replacements for concrete constituents (Albano et al, 2009), (Khalil and Mahdi, 2020). Reutilizing PW, especially resin-based types and PET, is a feasible substitute for natural sand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the burning of other forms of waste such as PET will release toxic gases. So, recycling appears to be the safest path for compliance with the ecosystem and economic gains (Albano et al, 2009). As a result, the recycling rate will be improving, and demand for natural raw material production will decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Most recycled poly(ethylene terephthalate) (R‐PET) flakes (>70%) are converted into fibers by mechanical recycling . Also, many studies have been performed on the use of PET wastes in different applications, such as bottles, films, sheets, modified concrete, and industrial parts, by the application of different modifications, such as blending, and through the creation of composites and nanocomposites . However, PET is a notch‐sensitive thermoplastic with a low impact strength that decreases during physical aging.…”
Section: Introductionmentioning
confidence: 99%